The "MANES project" and research on school textbooks - Somoza Rodríguez, Miguel (Avances en Supervisión Educativa, 2007)
Rather than the origin of the MANES Project of School Manuals, the author displays its objectives: the building up of a multi-section library and a wide database -made up my a well-supplied holding of School Manuals from Spain, the rest of Europe and Latin-America-, the development of research and document activities, the publishing of works under its protection, and the setting up of opportunities of cooperation between universities in Spain and in the rest of the world.Professor Miguel Somoza presents the assessments of the Project, which have led to an increase of knowledge about text-books as an intellectual and material good, to improve communication between researchers through meetings, summits and symposia, and to an exchange of information about text-books among different universities and institutions.The MANES project is really a must for the teaching society and especially for the National University for Non-Attendant Students, of which the History of Education Department decidedly encourages it.